Integration of Montessori Method with Role-Playing Activities to Enhance Character Development and Independence in Early Childhood - Nuraziza Aliah; Nurasia Natsir; Patmawati Halim; Asyima Asyima (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Character development and independence in early childhood constitute fundamental foundations for future life success. While both the Montessori method and role-playing activities have proven effective in early childhood education, research on their integration remains limited. To analyse the effectiveness of integrating the Montessori method with role-playing activities in enhancing character development and independence in early childhood. A quantitative study employing quasi-experimental design with pre-test and post-test control group design was conducted with 60 children aged 4-6 years. Participants were randomly assigned to an experimental group (n=30, receiving the integrated method) and a control group (n=30, receiving conventional instruction). Significant improvements were observed in both character development (p<0.05) and independence (p<0.01) in the experimental group. The experimental group showed substantial gains in character scores (18.94 points) compared to the control group (4.36 points), with large effect size (Cohen's d = 2.06). Independence scores increased by 21.23 points in the experimental group versus 4.47 points in the control group, also with a large effect size (Cohen's d = 2.65). The integration of Montessori method with role-playing activities proves highly effective in enhancing character development and independence in early childhood, offering a promising pedagogical approach for early childhood education.